2008
DOI: 10.1203/pdr.0b013e31817445b8
|View full text |Cite
|
Sign up to set email alerts
|

Schwann Cells From Human Neurofibromas Show Increased Proliferation Rates Under the Influence of Progesterone

Abstract: Neurofibromatosis type 1 (NF1) is a hereditary disease caused by mutations of the NF1 gene at 17q11.2. Loss of the NF1 gene product in Schwann cells leads to the development of benign nerve sheath tumors. These neurofibromas may occur at any time but tend to arise during periods of hormonal imbalance, suggesting that hormones influence neurofibroma growth. As steroid hormone levels rise during these times, we hypothesized that progesterone has proliferative effects on neurofibroma-derived Schwann cells. We cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 18 publications
(24 reference statements)
0
12
1
Order By: Relevance
“…12 There may be a differential cellular expression of progesterone receptors in humans and in mice, which could explain the observed differences in Schwann cell proliferation in each of these studies. Li et al 5 noted that they were unable to detect progesterone receptors in their xenografts, and we have also been unable to detect progesterone receptors in murine cells using western blot.…”
contrasting
confidence: 64%
See 1 more Smart Citation
“…12 There may be a differential cellular expression of progesterone receptors in humans and in mice, which could explain the observed differences in Schwann cell proliferation in each of these studies. Li et al 5 noted that they were unable to detect progesterone receptors in their xenografts, and we have also been unable to detect progesterone receptors in murine cells using western blot.…”
contrasting
confidence: 64%
“…Mast cell, fibroblast and Schwann cell cultures were derived from wild type (WT) and Nf1 haploinsufficient (+/-) mice and WT, Nf1 +/-and Nf1 knock out (-/-) embryos using our established methodologies. [7][8][9] In contrast to studies reported in human cells and tissues, [4][5][6] progesterone did not show any positive impact on proliferation of Nf1 mutated murine cells. Furthermore, the addition of progesterone to the Schwann cell cultures abrogated the glial growth factor (GGF) mediated gain in Nf1 -/-Schwann cell proliferation.…”
mentioning
confidence: 78%
“…In histological studies, receptors of growth or steroid hormones have been described on cutaneous NF, reinforcing their potential role in NF growth [8]. In vitro progesterone was shown to induce a higher proliferation rate of NF1-derived Schwann cells in comparison with non-NF1 human Schwann cells [9,10]. …”
Section: Discussionmentioning
confidence: 99%
“…Changes in steroid hormone production may affect the NF1 phenotype. Immunostaining studies have provided support for this hypothesis by identifying the progesterone receptor in neurofibromas [30]. Estrogen and progesterone increased the growth rate of MPNSTs xenografts in mice [31].…”
Section: Discussionmentioning
confidence: 99%